Nucleation of the "odil pontes" school: a view from parents and students from the Tomé-Açu community of Espirito Santo, PA - Evangelista de Oliveira, Celeste; Fabíola Evangelista de Oliveira, Antônia; Bentes Tavares, Francinei; Michelle Lima da Silva de Oliveira, Maria; Barros, Reginaldo; do Socorro Ferreira Sena, Patrícia; Lima Silva, Carla; Francisco da Silva Costa, José (Seven Editora, 2023)
The present work aims to reflect on the Nucleation of the Odil Pontes School, emphasizing a vision from the Parents and students of the Espirito Santo Community in the Municipality of Tomé Açu, Pa, that is, to show the main aspects that occurred in the transition from the school belonging to the community to the nucleated school. , searching through questionnaires to families and observations in the public education institution Odil Pontes, reflections of the reality experienced with the change of school location, evaluating the positive and negative points, such as transportation, teaching-learning process, physical structure of the school, policy public on the issue of school transport. Based on the information from the interviewees, we will seek to understand and analyze what difficulties will be faced due to the nucleation of the ODIL Pontes school and this change will represent for the teaching and learning process. To carry out the research, we opted for the case study where the methodological contribution is organized in a qualitative approach in which we used the interview with nine (9) residents of the community to understand the scenario involving the nucleation of the Odil Pontes school. The research concludes considering that with the nucleation, there was concern about school transport, changes in the daily life of families, involvement with the issue of local culture, an improvement in the teaching/learning process, but a certain neglect on the part of policy transportation, sometimes leaving it to the family to drive the community to school and vice versa. DOI: https://doi.org/10.56238/methofocusinterv1-118